Use of Information Technology in Central University Libraries of India - Ramana, P. Venkata; Rao, V. Chandrasekhar (DESIDOC Journal of Library & Information Technology, 2003)
Central University (CU) Libraries in India are currently at various stages of advancement in the use of information technology(IT). This paper presents the results of a research study conducted to survey the use of IT in CU libraries. It describes libraries collection, current periodicals, library staff, users, budget, and infrastructural facilities of CU libraries. It discusses planning approaches adopted for IT implementation, objectives of library automation, persons involved in library automation planning, steps taken for library automation implementation, factors considered in selecting library automation software, and constraints faced in library automation. It covers computers and software packages used, computerised library operations, development of databases, bibliographic standards used, computerised information services, level of participation in networks and computerised facilities offered to users, etc. The results summarized in this paper reflect the current trends and future plans relating to the use of IT in CU libraries. http://dx.doi.org/10.14429/dbit.23.2.3595